2018
DOI: 10.1111/ajpy.12199
|View full text |Cite
|
Sign up to set email alerts
|

Canine co‐therapy: The potential of dogs to improve the acceptability of trauma‐focused therapies for children

Abstract: Objective: Post-traumatic stress disorder is a debilitating syndrome that effects approximately 30% of those who experience childhood trauma. Whilst effective treatments exist, they have high rates of attrition and non-engagement. Augmenting traditional interventions such as trauma-focused cognitive behaviour therapy is an approach often used to address this problem. The current study aimed to assess the acceptability of a novel adjunct, canine-assisted therapy, which may be particularly useful with younger ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Studies which use animals in psychotherapeutic settings have had positive outcomes when treating adolescents with anxiety and depression (Wilson et al, 2017 ). Furthermore, some studies have found that therapy involving animals is more acceptable than medication when treating children with externalising behaviour problems (Dravsnik et al, 2018 ; Rabbitt et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies which use animals in psychotherapeutic settings have had positive outcomes when treating adolescents with anxiety and depression (Wilson et al, 2017 ). Furthermore, some studies have found that therapy involving animals is more acceptable than medication when treating children with externalising behaviour problems (Dravsnik et al, 2018 ; Rabbitt et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two separate studies have found parental perceptions of CAA to be positive, ranking dog-assisted psychotherapy as preferable to medication (Dravsnik et al, 2018 ; Rabbitt et al, 2014 ). However, these studies did not examine CAA in schools, nor differentiate between various CAA uses.…”
Section: Introductionmentioning
confidence: 99%